2021
DOI: 10.3390/toxins13050306
|View full text |Cite
|
Sign up to set email alerts
|

Shiga Toxin-Associated Hemolytic Uremic Syndrome: Specificities of Adult Patients and Implications for Critical Care Management

Abstract: Shiga toxin-producing Escherichia coli-associated hemolytic uremic syndrome (STEC-HUS) is a form of thrombotic microangiopathy secondary to an infection by an enterohemorrhagic E. coli. Historically considered a pediatric disease, its presentation has been described as typical, with bloody diarrhea at the forefront. However, in adults, the clinical presentation is more diverse and makes the early diagnosis hazardous. In this review, we review the epidemiology, most important outbreaks, physiopathology, clinica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
31
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 229 publications
(417 reference statements)
2
31
0
Order By: Relevance
“…The pathogenicity of STEC is mainly reliant on the development of one or two Shiga toxins (Stx1, Stx2), causing mild to severe symptoms of hemorrhagic colitis (HC). However, two major lethal syndromes, namely hemolytic uremic syndrome (HUS) and thrombotic thrombocytopenic purpura (TTP), have been reported as outcomes associated with STEC infection [13].…”
Section: Introductionmentioning
confidence: 99%
“…The pathogenicity of STEC is mainly reliant on the development of one or two Shiga toxins (Stx1, Stx2), causing mild to severe symptoms of hemorrhagic colitis (HC). However, two major lethal syndromes, namely hemolytic uremic syndrome (HUS) and thrombotic thrombocytopenic purpura (TTP), have been reported as outcomes associated with STEC infection [13].…”
Section: Introductionmentioning
confidence: 99%
“…The results of several epidemiological investigations reviewed by Kaper et al [ 3 ] have demonstrated the link between the occurrence of severe food-borne disease outbreaks, or even deaths, and the consumption of raw dairy products contaminated with different diarrheagenic E. coli strains. Studies focused mainly on monitoring the Shiga-toxin-producing E. coli (STEC) strains found in food matrices, due to their toxicity and infectious potential, related to the toxin productions (e.g., Stx1 or Stx2), which generate hemorrhagic colitis, as well as two other major lethal syndromes in human patients, namely, thrombotic thrombocytopenic purpura and hemolytic uremic syndrome [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…The resultant inflammatory reaction could help bacteria to form vascular tumors through the production of cytokines and vasoproliferative factors [ 1 ]. It could also induce endothelial damage, by a proinflammatory context and by activating the complement pathway, similar to the Shiga toxin–producing Escherichia coli –associated hemolytic uremic syndrome [ 8 , 9 ]. As previously described, Bartonella species partially escape complement activation by a modified lipopolysaccharide chain, but it is possible that immunocompromised hosts have higher bacterial load and complement activation occurs anyway [ 10 ].…”
Section: Discussionmentioning
confidence: 99%